The Impact of Counselling in Children’s Homes and Observation Homes on Drug Abuse- A Review: Exploring the impact of counselling on drug usage in youth residential facilities (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Drug abuse is a complicated problem with many social, cultural, biological, environmental,historical, and economic dimensions. Drug usage and teen aggression are strongly correlated. Socialisolation is one of the main factors contributing to adolescent misbehaviour. Delinquent behaviour isdescribed as aggressive behaviour against others. Delinquent behaviour that is hostile against siblings,friends, parents, teachers, or other people, such as verbal abuse, bullying, and hitting, is a concerningproblem. Child drug misuse may lead to high-risk behaviours for oneself and others, such as lying,stealing, secret property destruction, and more. Therefore, the current study's objective is to ascertainhow counselling in children's homes and observation homes affects drug usage.